1968
DOI: 10.1017/s0022112068002120
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of local pressure and skin friction around a circular cylinder in cross-flow up to Re = 5 × 106

Abstract: In a large range of Reynolds numbers, 6 × 104 < Re < 5 × 106, the flow around single cylinders with smooth surfaces has been investigated. The high values of the Reynolds numbers were obtained in a test channel which could be pressurized up to 40 bar of static pressure. New experiments were performed to measure the local pressure and skin friction distribution around the cylinder. From these results the total drag, the pressure drag and the friction drag were calculated. By means of the skin friction dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
262
5
8

Year Published

1969
1969
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(327 citation statements)
references
References 4 publications
(3 reference statements)
36
262
5
8
Order By: Relevance
“…Another experimental investigation made by Son and Hanratty (1969) determined a value of θ = 78º for the separation angle. A very interesting observation was made by Achenbach (1968) for Re = 1.0 x 10 5 (sub-critical flow): it was found that the laminar boundary layer separates at θ = 78º. Just before transition into the critical region at Re = 2.6 x 10 5 , the boundary layer is still laminar and separates at an angle equal θ = 94º.…”
Section: Simulations Of Unsteady Flows Past a Circular Cylinder Isolamentioning
confidence: 95%
“…Another experimental investigation made by Son and Hanratty (1969) determined a value of θ = 78º for the separation angle. A very interesting observation was made by Achenbach (1968) for Re = 1.0 x 10 5 (sub-critical flow): it was found that the laminar boundary layer separates at θ = 78º. Just before transition into the critical region at Re = 2.6 x 10 5 , the boundary layer is still laminar and separates at an angle equal θ = 94º.…”
Section: Simulations Of Unsteady Flows Past a Circular Cylinder Isolamentioning
confidence: 95%
“…The point of zero shear stress for the time-averaged flow is delayed ( θ zss = 107.6 • ) compared with the natural case, and the instantaneous stagnation point behind the separation vortex appears farther downstream ( θ stg ≈ 120 • -135 • ). These angles are still upstream of the turbulent separation point over a cylinder ( θ zss = 140 • reported by Achenbach 1968). The effects of the actuation become clear on comparing the time-averaged pressure fields between these two cases.…”
Section: Resultsmentioning
confidence: 70%
“…Due to the fact that 2 F has a fast decay far from the reference vortex, it is essential to calculate the length of the radial distance from the reference vortex that captures only those vortices actually exerting influence on the local turbulence around the reference vortex. The two other parameters that affect the turbulence model in addition to f 1 In order to analyze the effect of the turbulent parameters in our simulations, we carry out numerical experiments to investigate the external ring semi-thickness,  re , and the mean density of vortices per unit area,  r , defined as the number of vortices in the ring divided by the ring area, averaged over all the vortices in the cloud. First, the factor f 2 associated with  re is analyzed through its dependence on  r .…”
Section: Determination Of Turmentioning
confidence: 99%
“…The numerical results for the drag coefficient are compared in Fig. 11 with the experimental results of Achenbach (1968), obtained in a low-pressure wind tunnel (ND channel) and a pressurized wind tunnel (HD channel), for several aspect ratios of the cylinder (defined as the ratio of length to diameter). Achenbach, in turn, presents in his paper experimental results obtained by Wieselsberger (1923), Fage and Warsap (1930) and Roshko (1961).…”
Section: Drag Coefficient and Strouhal Number As A Function Of Reynolmentioning
confidence: 99%
See 1 more Smart Citation